Analysis of Nutritional Composition of Five Growing Waxy Vegetable Varieties In West Halmahera Regency North Maluku - Fitri Wahyu Wijayanti; Stevani B. Fara (Agrologia, 2021)
The wax vegetable plant (Saccharum edule) is a type of sugarcane plant, has many types and can be found in several regions in Indonesia. This study aims to determine the nutritional content of five varieties of vegetable Lilin cultivated in West Halmahera Regency North Maluku. This research is using experimental method. Using short white, long white, long white, red, short yellow and long yellow wax vegetables, which are cultivated in West Halmahera Regency, North Maluku. The variables observed included moisture content, fat content, protein content, ash and carbohydrate content. The results showed that the moisture content ranged from 87.59% - 91.76%, fat content ranged from 0.25% - 0.67%, protein content ranged from 3.19% - 4.17%, ash content ranged from 1, 40% - 1.56%, and the carbohydrate content ranges from 3.41% - 6.20%. In terms of nutritional content (fat, protein and carbohydrates), short yellow and long yellow varieties have a higher value.Keywords: Nutritional content, Candle Vegetables, West Halmahera